The Relationship of Consumption Purin-rich foods to the incident of Hyperuricemia in the Elderly at Hisosu Nursing Home In Binjai: The Relationship of Consumption Purin-rich foods to the incident of Hyperuricemia - Muselli, Angrayni Putri; Tala, Zaimah Z. (Talenta Publisher, 2020)
Hyperuricemia is an increase in blood uric acid levels. In the elderly cell damage occurs due to the aging process which can result in organ weakness, physical damage and various diseases such as increased uric acid levels. The purpose of this study is to determine the relationship between purine intake and the incidence of hyperuricemia in the elderly at the HISOSU Binjai nursing home. This research was conducted with an observational analytic research design using a cross sectional study. Samples were selected using the total sampling method and adjusted for inclusion and exclusion criteria. Data taken by weighing and recording food (in 1 day) Then assess respondent uric acid levels. This is done 3 times in the HISOSU Binjai nursing home. There are 32 research samples. Samples that experienced hyperuricemia as much as 40.6%, most of them consuming moderate-category purine source protein. The results of the chi-square test Pearson chi-squared t-test was 16.453 and p value < 0.001 (<0.05), it can be concluded as consumption of purine source protein associated with the incidence of hyperuricemia. The higher the purine intake, the greater the chance of getting hyperuricemia.